(untitled) (Journal of the College of Basic Education, 2026)
This research studies the referential tools in the Surah of Al-Qamar and their effect on the cohesion of the text; this is to contribute to the cohesion of the textual structure. The research has focused on the referential tools with the pronoun, the demonstrative noun, the relative pronoun, and the temporal and spatial circumstances, etc. The extent to which these tools are employed in the context of the Surah of Al-Qamar has a clear effect in bridging the gap between the verses of the Surah, as it gives the text of the Surah a linguistic and rhetorical cohesion, and a thematic unity that highlights the stylistic miracle in the Holy Quran, as the cohesion and systems are among the characteristics of the stylistic miracle in the Quranic text.. The research shows the aesthetic-rhetorical effect of the reference in shaping the textual fabric in five stories in the Surah, and it shows that the reference has a pivotal effect in guiding the understanding of the recipient by linking the previous parts with the latter, which enriches the interpretive experience and deepens the artistic appreciation of the text.. It has become clear from the textual and contextual references in the context of the Surah of Al-Qamar that the employment of these tools is eloquent, as it reflects the Quranic intentions in warning and reminding, and shows the dramatic structure that is based on the repetition of the intended and pictorial message for the purpose of destruction and denial. It also became clear that the referential tools are not just linguistic tools, but rather they are an effective structural mechanism in producing the Quranic text and its tight structure.